2007
DOI: 10.1016/j.neuroscience.2007.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Foxg1 expression by knock-in of Cre recombinase: Effects on the development of the mouse telencephalon

Abstract: The Cre/loxP system is used routinely to manipulate gene expression in the mouse nervous system. In order to delete genes specifically from the telencephalon, the Foxg1-cre line was created previously by replacing the intron-less Foxg1 coding region with cre, resulting in a Foxg1 heterozygous mouse. As the telencephalon of heterozygous Foxg1 mice was reported to be normal, this genotype often has been used as the control in subsequent analyses. Here we describe substantial disruption of forebrain development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 70 publications
8
78
0
Order By: Relevance
“…This is possibly due to the different expression patterns of Foxg1 and Hesx1, or is a potential additive effect due to Foxg1 haploinsufficiency in the Foxg1-Cre knock-in line used, as even heterozygous animals have telencephalic defects (Eagleson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly due to the different expression patterns of Foxg1 and Hesx1, or is a potential additive effect due to Foxg1 haploinsufficiency in the Foxg1-Cre knock-in line used, as even heterozygous animals have telencephalic defects (Eagleson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…B6.129-Tg(Pcp2-cre)2Mpin/J mice (Barski et al 2000), B6.CgTg(Nes-cre)1Kln/J mice (Tronche et al 1999), and B6.129P2(Cg)-Foxg1 tm1(cre)Skm /J mice (Eagleson et al 2007) were obtained from The Jackson Laboratories. These mice were backcrossed to the C57BL/6J strain (Jackson Laboratories) and were housed in a facility accredited by the American Association for Laboratory Animal Care.…”
Section: Micementioning
confidence: 99%
“…By E13.5, reporter expression was found throughout the otic lines are used. The most commonly used line is the depending on the strength of the fluorescent reporter COX ET.AL: Conditional Gene Expression in the Mouse Inner Ear Using Cre-loxP Pirvola et al 2002;Arnold et al 2006;Zelarayan et al 2007;Barrionuevo et al 2008;Jones et al 2008;Rickheit et al 2008;Grimsley-Myers et al 2009;Schultz et al 2009;Wang et al 2009;Yamamoto et al 2009;Deng et al 2010;Freyer and Morrow 2010;Haugas et al 2010;Hurd et al 2010;Hwang et al 2010;Sipe and Lu 2011 (Hebert and McConnell 2000), which has been reported to cause haploinsufficiency phenotypes that include proliferation in other organs (Shen et al 2006;Eagleson et al 2007;Siegenthaler et al 2008). However, no change in proliferation in the inner ear has been reported in several papers where proper controls of Foxg1-Cre mice (without the floxed allele) were used (Yamamoto et al 2009(Yamamoto et al , 2011Hartman et al 2010;Brown and Epstein 2011).…”
Section: Cre/creer Lines For the Developing Otic Vesicle And Otocystmentioning
confidence: 99%